2018
DOI: 10.1097/hpc.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and Atrial Fibrillation: Meta-analysis

Abstract: Hyperuricemia has been recently speculated to be associated with the development of atrial fibrillation (AF). A meta-analysis of observational studies was conducted to explore the relationship between serum uric acid (SUA) and AF. We searched the MEDLINE, EMBASE, and CINAHL databases and performed extensive bibliography search to identify studies with mean SUA level for patients with and without AF. Key search terms were "atrial fibrillation" and "uric acid." Under the random-effects model, the pooled standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“… 29 Studies have confirmed that uric acid can induce and aggravate atrial remodeling by enhancing inflammation and oxidative stress, and thereby triggering the occurrence of atrial fibrillation. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Studies have confirmed that uric acid can induce and aggravate atrial remodeling by enhancing inflammation and oxidative stress, and thereby triggering the occurrence of atrial fibrillation. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…29 Studies have confirmed that uric acid can induce and aggravate atrial remodeling by enhancing inflammation and oxidative stress, and thereby triggering the occurrence of atrial fibrillation. 30,31 Uric acid is the end product of purine metabolism, and xanthine oxidase is the rate limiting enzyme of its synthesis. A physiological concentration of uric acid has antioxidant properties, but when uric acid enters the cell or is in the acidic/hydrophobic environment of atherosclerotic plaque, the antioxidant properties will change, and it becomes a prooxidant.…”
mentioning
confidence: 99%
“…AF is the most common heart rhythm disorder, and its major risk factors include advanced age, hypertension, obesity, diabetes, HF, valvular heart disease, and MI. In recent years, numerous clinical studies have confirmed that hyperuricemia is associated with AF after adjusting for various cardiovascular risk factors, and the correlation is stronger in women than in men (Liang et al, 2016;Zhang et al, 2016;Chen et al, 2017;Kuwabara et al, 2017c;Mantovani et al, 2018;Pak et al, 2018;Black-Maier and Daubert, 2019;Lin et al, 2019). The bases for sex-related differences in high UA and AF or CHD remains unknown.…”
Section: Ua and Afmentioning
confidence: 99%
“…Considering the continuous rise in the average life expectancy in recent years and an increase in cardiac morbidity, the occurrence of AF has been increasing sharply in the past two decades. Despite advancements in the detection and management of AF, inadequate guidance persists, regarding primary prevention and risk stratification of this disease (6).…”
Section: Introductionmentioning
confidence: 99%